2009
DOI: 10.1097/mpg.0b013e31818f0a1f
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Video Capsule Endoscopy in the Management of Children With Peutz‐Jeghers Syndrome: A Blinded Comparison With Barium Enterography for the Detection of Small Bowel Polyps

Abstract: CE is a feasible, safe, and sensitive test for small bowel polyp surveillance in children with PJS. It is significantly more comfortable than BE and is the preferred test of most children for future surveillance. There is a learning curve for reporting CE studies in PJS and appropriate training is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 30 publications
(76 reference statements)
1
31
0
3
Order By: Relevance
“…Two studies in adult patients found that video capsule endoscopy (VCE) has a greater sensitivity in detecting small bowel polyps [33,34], although the study size was small in both studies. A prospective study has been performed comparing BaFT and VCE in paediatric patients with PJS [35]. No significant difference was found in detection rates of polyps [1 cm but VCE detected more polyps \1 cm and also was much better tolerated.…”
Section: Mode Of Surveillancementioning
confidence: 95%
“…Two studies in adult patients found that video capsule endoscopy (VCE) has a greater sensitivity in detecting small bowel polyps [33,34], although the study size was small in both studies. A prospective study has been performed comparing BaFT and VCE in paediatric patients with PJS [35]. No significant difference was found in detection rates of polyps [1 cm but VCE detected more polyps \1 cm and also was much better tolerated.…”
Section: Mode Of Surveillancementioning
confidence: 95%
“…Capsule enteroscopy is a feasible, safe and sensitive test for small bowel surveillance in patients with PJS, even in children. It is significantly more comfortable than barium enterography [86,87] . The use of capsule endoscopy permits earlier diagnosis, therefore, the clinical course of intestinal polyps has changed.…”
Section: Screeningmentioning
confidence: 99%
“…In specialized centers, CE is used to identify large polyps and to apply BE to remove them. 27,28 The effect on the incidence of intussusceptions remains to be established in prospective trials, though. 29 Adenoma or adenocarcinoma were observed in 9 of 30 polyps (30.0%) > 20 mm and in 1 of 80 polyps (1.3%) ≤20 mm and were resected endoscopically.…”
Section: Endoscopic Resection Of Small Intestinal Polyps Stricture Dmentioning
confidence: 99%